2020
DOI: 10.1186/s12935-020-01175-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk scoring system for evaluating the prognosis of patients with Her2-positive breast cancer

Abstract: Background: As one of the many breast cancer subtypes, human epidermal growth factor receptor 2 (Her2)-positive breast cancer has higher invasiveness and poor prognosis, although the advent of anti-Her2 drugs has brought good news to patients. However, the emergence of drug resistance still limits its clinical efficacy, so there is an urgent need to explore new targets and develop a risk scoring system to improve treatments and evaluate patient prognosis.Methods: Differentially expressed mRNAs associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Two human DGAT isoforms have been described (182). The expression of DGAT2 in HER2-positive breast cancer was decreased and was closely related to patient prognosis (140). However, data from TCGA reported DGAT2 as an unfavorable prognostic factor for endometrial cancer ( Table 1).…”
Section: Fatty Acid-related Alterations As Biomarkers Of Cancer Prognmentioning
confidence: 99%
“…Two human DGAT isoforms have been described (182). The expression of DGAT2 in HER2-positive breast cancer was decreased and was closely related to patient prognosis (140). However, data from TCGA reported DGAT2 as an unfavorable prognostic factor for endometrial cancer ( Table 1).…”
Section: Fatty Acid-related Alterations As Biomarkers Of Cancer Prognmentioning
confidence: 99%
“…Wang et al [ 31 ] identified a six differentially-expressed genes (DEGs) model consisting of IGHA2, SERPINA1, GFALS, SPDYC, PAX7, and ADRB1 by using Cox regression survival modeling for breast cancer. In another study [ 32 ], the authors constructed a prognostic risk scoring system containing 6 genes (SCUBE3, RDH16, SPC24, SPC25, CCDC69 and DGAT2), suggesting that these mRNAs may serve a driving role in the progression of Her2-positive BC. The construction of this risk scoring system is conducive to identifying high-risk HER2-positive BC patients, and it subserve to help achieve personalized targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The univariate analysis shows that CCDC69 is a low-risk factor for breast cancer. 17 It can be seen that the high expression of CCDC69 is a protective factor for the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%